Speech evaluation in children with missing anterior teeth and after prosthetic rehabilitation with fixed functional space maintainer - Garima Kalia; Sandeep Tandon; Nameksh Raj Bhupali; Ambika Rathore; Rinku Mathur; Khushboo Rathore (Wolters Kluwer Medknow Publications, 2018)
Introduction: Speech and language development in children is a dynamic process. Development of vocal sound into meaningful speech was one of the major discoveries which have made the human beings to reach the pinnacle of the animal kingdom. The ability to speak is determined by the flow of air into the mouth which affects pronunciation of various words and phrases. Aim: This study aimed to evaluate speech changes before and after prosthetic rehabilitation with fixed functional space maintainer in children with missing maxillary anterior teeth. Materials and Methods: The study sample comprised of 25 children in the age range of 3-6 years having at least two maxillary anterior teeth indicated for extraction or had already got extracted. Speech therapist evaluated articulation of [v], [ph], [n], [d], [dh], [th], [t], [s.],[s], and [l] speech sounds of patients preoperatively (T0), postoperatively after the appliance insertion (T1), and postoperatively after 7 days (T2) using Weiss Comprehensive Articulation Test. The data obtained were analyzed using Chi-square and Mcnemar's test. Results: There was statistically significant (P < 0.05) correction in [v], [ph], [d], [dh], [th], [t], [s.], and [s] speech sounds immediately after prosthetic rehabilitation (T1). While, the assessment of speech sounds after 7 days of appliance insertion (T2) showed statistically nonsignificant differences. Conclusions: The results suggested that treatment of a patient with missing anterior teeth should not be restricted to esthetic and functional oral rehabilitation, but also comprehend with the speech, as premature loss of the primary maxillary incisor appears to have long-term effect on the speech development.